Macular Function in Early and Intermediate Age-related Macular Degeneration: Correlation with the Simplified Thea Risk Assessment Scale (STARS) - Minnella, Angelo Maria (Transl Vis Sci Technol, 2020)
PURPOSE: Early detection of retinal dysfunction in age-related macular degeneration (AMD) may be important for both prevention and treatment. The aim of this study was to evaluate in early and intermediate AMD the correlation of macular function, assessed by the focal electroretinogram (fERG), with the Simplified Thea Risk Assessment Scale (STARS), a simple 13-item self-administered questionnaire. METHODS: We recorded a fERG (18°, 41 Hz) in 84 patients with AMD (40 male and 44 female, age 55–87 years, visual acuity 20/40–20/20), who had undergone a 5-year clinical ophthalmic and general follow-up. Sixty-six patients had early and 17 patients intermediate AMD. Fifty healthy subjects, in a comparable age range, served as controls. The fERG amplitude (in microVolts) was the main outcome variable. STARS was calculated for each patient. RESULTS: Compared with controls, fERG amplitudes were significantly reduced, on average, in both early and intermediate patients with AMD (P < 0.01). In both groups, fERG amplitudes tended to decrease with age and to increase with visual acuity and were negatively correlated with STARS (early r = –0.6, P < 0.01; intermediate, r = –0.50, P < 0.05). fERG losses were greatest in patients with a STARS score of greater than 20. CONCLUSIONS: In early and intermediate AMD, STARS robustly predicted central retinal function, as assessed by fERG, supporting the combined use of both parameters to estimate the clinical risk of visual function loss. TRANSLATIONAL RELEVANCE: The STARS may predict macular function in AMD and could be used in the daily clinical practice to estimate the risk of visual function loss in early disease stages.